1958
DOI: 10.1039/jr9580000360
|View full text |Cite
|
Sign up to set email alerts
|

66. Studies in relation to biosynthesis. Part XIII. Griseofulvin

Abstract: Me*14C0,H, when fed to a strain of Penicilliuwa griseofulvuin Dierckx, This result A preliminary leads to griseofulvin with the isotopic distribution shown in (I).supports the general validity of the acetic acid hypothesis. account of some of this work has already appeared.1 STRUCTURAL evidence reviewed in Part I suggested-that the skeletons of many natural phenolic compounds are derived, at least in part, by the head-to-tail linkage of acetic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

1959
1959
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…Based on the observations of incorporation of seven units of [1-14 C]acetic acid into griseofulvin, Birch et al in 1958 supported the "acetic acid hypothesis", suggesting that the core ring structure of many phenolic compounds were derived by head-to-tail linkage of acetic acid units. 79 This theory was later revised as 13 C NMR studies clarified that only the starter unit of the growing polyketide chain is derived from acetic acid, whereas the sequential chain extension resulting in the intermediate 6 (see Scheme 1), the precursor for the two first ring formations, uses six malonate units during extension of the polyketide chain. 80 A phenoxyl radical cyclization mechanism for the formation of the core grisan ring of griseofulvin was suggested by Barton and Cohen in 1957.…”
Section: Fungal Biosynthesis Of Griseofulvinmentioning
confidence: 65%
“…Based on the observations of incorporation of seven units of [1-14 C]acetic acid into griseofulvin, Birch et al in 1958 supported the "acetic acid hypothesis", suggesting that the core ring structure of many phenolic compounds were derived by head-to-tail linkage of acetic acid units. 79 This theory was later revised as 13 C NMR studies clarified that only the starter unit of the growing polyketide chain is derived from acetic acid, whereas the sequential chain extension resulting in the intermediate 6 (see Scheme 1), the precursor for the two first ring formations, uses six malonate units during extension of the polyketide chain. 80 A phenoxyl radical cyclization mechanism for the formation of the core grisan ring of griseofulvin was suggested by Barton and Cohen in 1957.…”
Section: Fungal Biosynthesis Of Griseofulvinmentioning
confidence: 65%
“…Cyclization to [2][3][4][5][6][7][8][9][10][11][12][13] C]cyclohexane-1,3-dione 7 was successful in dry tetrahydrofuran, using carefully dried potassium tert-butoxide 7 The desired product 8 was isolated in a 70% yield after purification.…”
Section: Resultsmentioning
confidence: 99%
“…After reaction with sodium ethoxide (formed in situ from sodium and ethanol) at 1351C for 4 h, phloroglucinol dicarboxylic acid diethyl ester 4 was hydrolysed in refluxing potassium hydroxide solution to yield the tri-labelled phloroglucinol 1a in 33% yield over the two steps. [2,4,[6][7][8][9][10][11][12][13][14] C 3 ]phloroglucinol was also obtained by Birch et al 3 during their biosynthetic studies on the incorporation of 14 C-labelled acetic acid into griseofulvin. We previously developed a synthetic route to [2-13 C]resorcinol 2a, where the phenol was constructed from acyclic precursors, using [ 13 C]methyl iodide as the source of isotopic label.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Feeding studies with P. griseofulvum showed that 9 is constructed from a linear chain of seven acetates. 106 Rhodes and coworkers at Glaxo experimented with fermentation conditions which led to the production of putative precursors of 9. For example limiting chloride concentration in the media led to the production of various griseophenones 105-106 and 111, while inhibiting C 1 metabolism gave different methylation isomers 105-108.…”
Section: Griseofulvinmentioning
confidence: 99%